2019
DOI: 10.1021/acsaem.8b02087
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Performance of Ni-Mo Alkaline Hydrogen Evolution Electrocatalysts with Carbon Supports

Abstract: Alkaline water electrolysis offers the use of low-cost active materials and ancillary components, making it attractive for hydrogen production from renewables. Nevertheless, the practical performance of nonprecious electrocatalysts for alkaline hydrogen evolution still lags behind platinum-group metals. This disparity motivates work to understand how the solid-state chemistry of nonprecious transition metal alloys influences their activity toward alkaline hydrogen evolution. To this end, we have clarified the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 84 publications
1
39
0
Order By: Relevance
“…34 Recently, a mixed phased catalyst, composed of crystalline Ni-rich Ni-Mo alloy nanoparticles embedded in a Mo-rich oxide matrix was prepared by Patel and co-workers. 35 This material has low activity toward hydrogen evolution. However, its activity markedly increased upon activation by postdeposition reductive annealing or by including carbon black as a catalyst support.…”
Section: Pgm-free Electrocatalystsmentioning
confidence: 99%
“…34 Recently, a mixed phased catalyst, composed of crystalline Ni-rich Ni-Mo alloy nanoparticles embedded in a Mo-rich oxide matrix was prepared by Patel and co-workers. 35 This material has low activity toward hydrogen evolution. However, its activity markedly increased upon activation by postdeposition reductive annealing or by including carbon black as a catalyst support.…”
Section: Pgm-free Electrocatalystsmentioning
confidence: 99%
“…Up to now, a wide range of materials, including transition metal alloys, transition metal carbides, transition metal dichalcogenides, transition metal phosphides, and so on, has been studied as possible alternative HER electrocatalysts. Among them, molybdenum disulphide (MoS 2 ) has attracted great attention due to its unique crystal structure and properties .…”
Section: Introductionmentioning
confidence: 99%
“…A catalyst mass loading of 50 µg/cm 2 was used throughout these measurements to minimize the confounding effects of electrical resistance associated with thicker films containing significant residual oxide. 25 The catalytic activity increased initially up to 400 • C and then decreased significantly at higher reduction temperatures. This trend is consistent with the TPR measurements, where two distinct chemical transformations were observed below and above 400 • C.…”
Section: Resultsmentioning
confidence: 95%
“…We recently reported that thermal reduction of compositionally homogeneous Ni-Mo oxide precursors results in spontaneous phase segregation into a core-shell nanocatalyst with excellent alkaline HER activity. 25 This result is intriguing for several reasons: first, the thermodynamically stable product under these treatment conditions is a single intermetallic with the empirical formula Mo 7 Ni 7 rather than the observed mixture containing a face-centered cubic (fcc) alloy and a mixed oxide. [26][27][28][29][30] Second, applying the same thermal reduction treatment to Mo oxide alone does not yield metallic Mo, but instead the sub-oxide MoO 3-δ .…”
Section: Introductionmentioning
confidence: 99%